1996
DOI: 10.1089/neu.1996.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Neurological Deficit in Mice with Traumatic Brain Injury by Nitric Oxide Synthase Inhibitors

Abstract: This study investigates the effect of the NO synthase inhibitors, NG-nitro L-arginine methyl ester (L-NAME) and 7-nitro indazole (7-NI), on the neurological deficit 24 h after a moderate closed head injury in mice. Low doses of L-NAME or 7-NI given soon after the injury significantly reduced the neurological deficit compared to the vehicle-treated group. L-Arginine (300 mg/kg) did not alter the neurological deficit, but reversed the protective effects of both L-NAME and 7-NI when given at the same time. Both L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Both penicillamine (Hall et al, 1999) and tempol (Beit-Yannai et al, 1996) have been reported to improve neurological recovery in rodent TBI models. Moreover, administration of the NOS inhibitors nitro-arginine methyl ester and 7-nitroindazole have been shown to improve neurological recovery in head-injured mice (Mesenge et al, 1996) together with a reduction in brain 3NT levels (Mesenge et al, 1998).…”
Section: Sources Of Peroxynitritementioning
confidence: 99%
“…Both penicillamine (Hall et al, 1999) and tempol (Beit-Yannai et al, 1996) have been reported to improve neurological recovery in rodent TBI models. Moreover, administration of the NOS inhibitors nitro-arginine methyl ester and 7-nitroindazole have been shown to improve neurological recovery in head-injured mice (Mesenge et al, 1996) together with a reduction in brain 3NT levels (Mesenge et al, 1998).…”
Section: Sources Of Peroxynitritementioning
confidence: 99%
“…Nitric oxide (NO) has been suggested to play a role in damage, recovery, or both after brain injury Mesenge et al, 1996;Holscher, 1997). Three different systems are reportedly involved in NO synthesis.…”
Section: Nitric Oxidementioning
confidence: 99%
“…However, the exact role of elevated NO after injury remains controversial. Inhibition of NO synthase has been shown to increase mortality22 and also reduce neurological deficits23 after experimental contusion in rats. It is possible that different isoforms of NO synthase may have different roles.…”
Section: Introductionmentioning
confidence: 99%